"Mediator Dei", Odo Casel e Pius Parsch - Premoli, Daniele (Römische Quartalschrift für christliche Altertumskunde und Kirchengeschichte, 2023)
"Mediator Dei, Odo Casel and Pius Parsch. On the Critical Objectives of the Encyclical De Sacra Liturgia" - The publication of the encyclical on the liturgy Mediator Dei (1947) was greeted with surprise and satisfaction by the liturgical movement. Some of its formulations, however, lent themselves to some misunderstandings, particularly in relation to the relationship with Odo Casel’s Mysteriengegenwart. Through the examination of the preparatory documents of the encyclical and some later interventions of the Holy Office, thanks to the opening of the vatican archives of the pontificate of Pius XII, this article aims to explore the relationship between the Holy See and two exponents of the liturgical movement: Pius Parsch and Odo Casel.